Comparative genomics and expression analysis of the CIPK gene family in rice (Oryza sativa) and foxtail millet (Setaria italica) - Hu, Zhao; Qian, Run; Xie, Fengpu; Wang, Ziwei; Yan, Pingmei; Yang, Jing (Frontiers in Plant Science, 2026)
The CIPK (CBL-interacting protein kinase) gene family serves as a crucial component of calcium-mediated signaling pathways in plants, playing vital roles in abiotic stress responses and developmental regulation. Despite their functional importance, systematic comparative analyses of CIPK gene families between cereal species with distinct physiological adaptations remain limited. To address this knowledge gap, we present a comprehensive comparative genomic analysis of CIPK gene families in two ecologically and physiologically divergent cereal crops - rice (Oryza sativa, a C3 species adapted to aquatic environments) and foxtail millet (Setaria italica, a C4 species with superior drought tolerance). We identified 33 and 35 CIPK genes in rice and foxtail millet, respectively, revealing conserved synteny but distinct evolutionary trajectories. Chromosomal mapping showed uneven distributions of CIPK genes in both species. Segmental duplications may have significantly contributed to family expansion (20/33 genes in rice; 19/35 in foxtail millet). Phylogenetic analysis classified members into six clades in foxtail millet and rice. Structural analysis revealed clade-specific exon-intron patterns, with complex architectures (12–20 exons) in Clade I versus simplified structures (1–3 exons) in other clades. Comparative genomics identified 26 orthologous pairs, though some genes (e.g., OsCIPK27) lacked detectable orthologs, indicating species-specific gene loss. Notably, foxtail millet CIPK exhibited lower instability indices, which may indicate potential stability differences. In addition, foxtail millet showed complete conservation of calcium-sensing NAF domains, whereas rice showed one NAF-deficient member (OsCIPK4). Promoter analysis identified species-specific cis-element enrichment: rice CIPK were enriched in drought/ABA-responsive elements, whereas foxtail millet showed greater light-responsive motif diversity. Expression profiling revealed tissue-specific patterns, with foxtail millet displaying more leaf-preferential expression (10 genes vs. 7 in rice), potentially linked to C4 photosynthesis. Under abiotic stress conditions, rice CIPK genes exhibited strong responses to both salt and cold stressors, whereas foxtail millet CIPK showed greater responsiveness to drought, mirroring their ecological adaptations. These findings provide novel insight into the potential function and evolutionary diversification of calcium signaling components (CIPK) in C3 and C4 cereals. They also provide important potential targets for improving the stress resistance of cereal crops.